Managing madness, murderers and paedophiles: understanding change in the field of English forensic psychiatry - McDonald, Ruth; Furtado, Vivek; Völlm, Birgit (Emerald, 2016)
This paper discusses changes occurring in the field of English forensic psychiatry which appear to be linked to feelings of discomfort amongst medical professionals who manage care in such settings. These changes are neither the result of a sudden ‘shock’ to the system, nor small improvisations at the margins, but instead appear to reflect a growing perception amongst psychiatrists of accepted field practice as inadequate for some types of patients. To understand how feelings and emotions are implicated in these changes we draw on and develop the work of Pierre Bourdieu to suggest that changes must be seen in the context of field tensions, which have implications for habitus. However, we do not view feelings of discomfort merely as a response to these tensions. Instead we suggest a more dynamic process with the habitus playing a key role in structuring what people pay attention to and how they perceive it, as well as whether they experience particular feelings in the first place, therefore.